IMF Staff papers : Volume 44 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1997)
The Chilean pension reform of 1981, a shift from cm unfunded to a funded scheme, is considered to have contributed to this country's excellent economic performance. Positive growth effects allow, in principle, a Pareto-improving shift in pension financing. This paper highlights the theoretical underpinnings of the reform and presents empirical data and preliminary econometric testing of the conjectured reform effects on financial market developments, as well as the impact on total factor productivity. capital formation, and private saving. The empirical evidence is consistent with most but not all claims. In particular, the direct impact of the reform on saving was low, and initially even negative.